(untitled) (Research, Society and Development, 2020)
They are increasing in the sporting context the investigations on the virtues of the human being, from the positive psychological. Moreover, besides these intrapersonal factors, the social interactions established in training and competitions have been essential for the personal growth and performance of athletes and coaches. This study aimed to investigate the coach-athlete relationship and the hope of athletes. Participated in this study 101 university athletes of different individual modalities, of both gender (20,48±2,54 years), participants of the 56th Paraná University Games (JUPs). Were used the Dispositional Hope Scale (DHS) and the Coach-Athlete Relationship Questionnaire (CARTQ) - athlete version. Data were analyzed using the Shapiro Wilk, Mann Whitney, Kruskall-Wallis and Spearman correlation coefficients (p<0,05). High values were found in almost all dimensions of the coach-athlete relationship, with emphasis on the closeness dimension (Md=6,5), followed by the complementarity dimension (Md=6,0), only the dimension commitment presented a significant difference from the others, presenting a lower level (Md=5,3). Both dimensions of hope presented high values (Md=16,0), and overall hope (Md=32,0). When verifying the correlations between hope and the coach-athlete relationship, there were positive correlations in all dimensions, with emphasis on the correlation between commitment and agency, as well as commitment and global hope, and also between complementarity and global hope (p<0,05). It is concluded that individual athletes from Paraná have a positive perception of the relationship with their coaches and are hopeful, showing motivational cognitive abilities and positive performance to achieve their goals.